2013
DOI: 10.1177/1941738113480464
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility for Depression in Current and Retired Student Athletes

Abstract: Background:Depression, a disabling mental disorder, adversely affects work, sleeping and eating habits, and family. Research does not exist on depression among athletes who have recently graduated from college and retired from their sport after exhausting their collegiate eligibility.Hypothesis:Changes in lifestyle and loss of personal identity, which follow college athletics, would put former college athletes at an increased risk for depression.Methods:A survey was sent to former (n = 163) and current (n = 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 7 publications
0
49
1
2
Order By: Relevance
“…The observed rate of 33.2% supported the hypothesis that the rate of depression symptoms in college athletes is higher than has been reported in previous studies of this population. These studies have shown the prevalence rate to range from 14%-23.7%, depending on the methods and measures used [3,46,47]. The discrepancy between the results obtained in this study and previous findings suggests that depression may be an issue that affects far more college athletes than previously thought.…”
Section: Overall Depression Prevalencecontrasting
confidence: 57%
See 3 more Smart Citations
“…The observed rate of 33.2% supported the hypothesis that the rate of depression symptoms in college athletes is higher than has been reported in previous studies of this population. These studies have shown the prevalence rate to range from 14%-23.7%, depending on the methods and measures used [3,46,47]. The discrepancy between the results obtained in this study and previous findings suggests that depression may be an issue that affects far more college athletes than previously thought.…”
Section: Overall Depression Prevalencecontrasting
confidence: 57%
“…Current prevalence of depression symptoms among NCAA division I athletes is as high or higher than the rate of 14%-21% observed in previous studies [3,44,46].…”
Section: Current Studymentioning
confidence: 47%
See 2 more Smart Citations
“…Many of the primary relationships (e.g., teammates, coaches) decrease substantially after graduation, resulting in a dissipating support network at the completion of college athletics (Weigand, Cohen, & Merenstein 2013). The strain resulting from lack of social support has been linked to lower levels of wellness (Dalgard & Tambs 1995;Watson 2015).…”
mentioning
confidence: 99%